„Et Land, hvortil nordiske Traditioner altid have knyttet sig“. Kampen om Grønlands 1855-56 - Wendel-Hansen, Jens Lei (Historisk Tidsskrift, 2017)
„A country that has always been connected to Nordic traditions“. The Fight for Greenland 1855-56 This article suggests that the debate on whether Greenland has ever been a Danish colony has often been influenced by later colony definitions mirroring the highly complex and ever-changing constitutional relationship between Greenland and Denmark. In 1855-56 it was discussed in the Danish parliament whether Greenlandic internal affairs should remain subject to the decision-making of the assembly of the Danish June Constitution of 1849 – the Rigsdag – whose authority was limited to the affairs of the kingdom of Denmark proper, or whether they should be regulated by the so-called Rigsråd, an assembly dealing with the common affairs of the complete Danish monarchy, including the German duchies Schleswig, Holstein and Lauenburg. By examining this debate, it is clear that the majority of Danish politicians did not agree with the government’s view that Greenland as a colony ought to be transferred to the common constitutional institutions, i.e. the Rigsråd. Such leading characters as N.F.S. Grundtvig and Frederik Hammerich argued that Greenland was not really a colony, but a biland, a dependency, which was included under the June Constitution and thus under the authority of the Rigsdag. This view was supported by the claim that, historically, Greenland was a country connected to the North, in opposition to Germany; and that the German subjects of the monarchy, the Germans in Holstein, should have no influence over Greenlandic affairs. Greenland thereby became a Danish national symbol – a symbol of the free democratic North as opposed to the unfree, aristocratic Germany. Greenland was more than an investment object, like the Danish West Indies, for instance, and should not be reduced to colony status. This analysis shows the dangers of retrospective statements that Greenland was simply a Danish colony. To most of the members of the Rigsdag in 1856, it certainly was not. The result of the debate was that the parliamentary opposition won the day and that Greenland remained subject to regulation by the Rigsdag.